2016
DOI: 10.35448/jte.v11i2.4331
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Penerapan Coso, Penerapan GCG Di Perusahaan Yang Berbasiskan Teknologi Informasi Untuk Memperoleh Kinerja Operasional Dan Kinerja Keuangan Yang Berkualitas

Abstract: Due to increasing global competition, many enterprises are aware of the benefits of Enterprise Resource Planning. This study is focuses on aspects of the ERP utilized in manufacturing industries. This paper report on one suit case study application. The case was conducted by using interview and observation techniques. The Situation-Actor-Process (SAP) paradigm was used to analyze the case. A synthesis was performed in the management context, situational factors, processes used in ERP system and the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The result of this study support the prior studies by Morris (2011), Catalya and Hadiprajitno (2014), Puspandoyo, (2015), and Julisar (2016 indicate that firms already have implemented ERP systems tend to report fewer internal control weaknesses than firms that do not have implemented ERP. Based on the results of logistic regression, it was found that implementing ERP had a significant effect only on general internal control weaknesses but not on specific internal controls, because Indonesia firms that already have implemented ERP did not optimize the control features of ERP.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The result of this study support the prior studies by Morris (2011), Catalya and Hadiprajitno (2014), Puspandoyo, (2015), and Julisar (2016 indicate that firms already have implemented ERP systems tend to report fewer internal control weaknesses than firms that do not have implemented ERP. Based on the results of logistic regression, it was found that implementing ERP had a significant effect only on general internal control weaknesses but not on specific internal controls, because Indonesia firms that already have implemented ERP did not optimize the control features of ERP.…”
Section: Resultssupporting
confidence: 88%
“…The use of ERP in firm operations will increase supervision in the system. Alzoubi (2011) and Julisar (2016) found that ERP systems' use improves the firm's internal control functions, especially for operational activities in finance and accounting. The use of an ERP system is useful to ensure the implementation of firm operational transactions run correctly and smoothly.…”
Section: Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The COSO ERM process can create informative communication so that it can connect the entire COSO ERM process more effectively and efficiently. This is in accordance with the research of Julisar (2016) which states that information and communication are important means for firm to ensure that the implementation of internal control on risk management is in accordance with those determined by the firm. The application of COSO's ERM at Sayurbox is also considered to be able to reduce costs arising from risks.…”
Section: Introductionsupporting
confidence: 86%